2013
DOI: 10.5505/tjb.2013.93898
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in the activity and expression of manganese superoxide dismutase, and mitochondrial oxidant generation in female and male rats

Abstract: Objective: The aim of this study was to examine the age-and gender-related differences in peroxide production, manganese superoxide dismutase (MnSOD) activity and expression in liver mitochondria of Wistar rats at 12 and 24 months of age. Methods: The chemiluminometric method for peroxide production, fluorometric method for malondialdehyde (MDA) levels, cumene hydroperoxide assay for glutathione peroxidase (GPx), the nitroblue tetrazolium assay for MnSOD activity, and Western-blotting for MnSOD expression were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…Our findings also showed that MnSOD enzyme gene expression had not significantly increased in active men, however, MnSOD gene expression changes were significant in women. These findings are consistent with those obtained by Ademoglu et al The investigators reported that MnSOD activity is higher in women than in men ( 39 ). Therefore, it is likely to indicate the higher influence of estrogen on MnSOD ( 37 ).…”
Section: Discussionsupporting
confidence: 93%
“…Our findings also showed that MnSOD enzyme gene expression had not significantly increased in active men, however, MnSOD gene expression changes were significant in women. These findings are consistent with those obtained by Ademoglu et al The investigators reported that MnSOD activity is higher in women than in men ( 39 ). Therefore, it is likely to indicate the higher influence of estrogen on MnSOD ( 37 ).…”
Section: Discussionsupporting
confidence: 93%
“…A significant negative correlation was obtained between SOD activity and the duration of the schizophrenic disease [32]. In an animal model it was shown (Wistar rats) that mitochondrial SOD and GPx activities remaind unaltered between 12 and 24 months Superoxide Dismutase in Psychiatric Diseases DOI: http://dx.doi.org/10.5772/intechopen.99847 of age, with no difference between two genders, while the gender and age-differences were observed in MnSOD expression [42]. Schizophrenic patients with tardive dyskinesia (TD) showed lower plasma MnSOD activity [43], CuZnSOD activity and total antioxidant status levels, but higher MDA levels than those without TD.…”
Section: Superoxide Dismutase and Psychiatric Diseases 31 Superoxide ...mentioning
confidence: 93%